Investigation of models of unilateral pathological processes of breach of local renal blood flow in order to determine changes in the status of the contralateral kidney: immunomorphological aspects. - Stus, V. P.; Barannik, K. S.; Shponka, I. S.; Poslavska О. V. (Морфологія / Morphologia / Morfologìâ, 2014)
Background. Morphology of compensatory-adaptive changes and their dynamics in a single remained kidney are still not clarified. Therefore, the study of renal parenchyma lesions in rat models of the most common pathological states has a great practical importance. Objective. To investigate the models of unilateral pathological processes of breach of local renal blood flow (ischemia, infringement of urodynamics) in order to determine changes in the status of the contralateral kidney. Methods. In the experiment on white Wistar rats permanent ischemia was modeled by a fixed bending left kidney artery (15 individuals – group A), acute infringement of urodynamics was modeled by a fixed crossing of the left ureter kidney ( 4 individuals – group B) and both pathological conditions were simulated (5 individuals – group C). Kidneys of 10 relatively healthy rats were used as a control. The primary monoclonal antibodies for CD3 and aSMA (TermoScientific, USA) were used. Results. The main pathological manifestations in the contralateral right "healthy" kidneys was in degenerative changes in epithelial tubule cells, foci of edema and sclerosis around large vessels, interstitial and perivascular inflammatory infiltrates containing CD3+ T-cells (for A II – 10,3±1,2, for B II – 11,9±1,1, for C II – 10,9±0,8). It differs significantly from the control group (p<0,05), where CD3+ T-lymphocytes occurred as single cells of interstitium. Conclusions. Unilateral damage of the kidney due to experimental ischemia, or infringement of urodynamics, or both pathological conditions, affecting local renal blood flow, results in pathological changes in the contralateral "healthy" kidney prior to the nephrectomy and suggests the importance of its medicament support.